Droughts, distress and a conditional cash transfer program to mitigate the impact of drought in Bihar, India - Kishore, Avinash; Joshi, Pramod Kumar; Pandey, Divya (International Association of Agricultural Economists, 2015)
Paddy- Bihar's staple crop- is vulnerable to droughts, primarily due to high cost of irrigation. In 2008, Bihar government launched a conditional cash transfer scheme to subsidise diesel for irrigation in drought affected areas. We show that this scheme has not been effective in mitigating the impact of drought on paddy production. A primary survey of potential and actual beneficiaries shows that low awareness and penetration among smallholders, alongside uncertainties and delays in the discursal of the subsidy, make it ineffective. We suggest that in states with limited capacity, such ad-hoc subsidies are unlickely to protect smallholders from weather shocks. Kishore, Avinash; Joshi, Pramod K.; Pandey, Divya